Propeller Flaps for the Anterior Trunk - Ogawa, Rei (Seminars in Plastic Surgery, 2020)
Various types of propeller flaps from multiple donor sites can be used to reconstruct anterior trunk skin defects. The actual selection depends on the condition and location of the recipient site, especially if it is to be the chest or abdomen that requires attention. Before surgery commences, it is always important to use an imaging analyses such as computed tomography angiography to examine and identify perforators that could perfuse a perforator-pedicled propeller flap (PPPF), as it is the most multifaceted imaging technique. Clusters of perforators that can be commonly used for the “workhorse” PPPFs for the thoracic and abdominal regions are the internal mammary artery perforator, the musculophrenic artery perforator, and the deep inferior epigastric perforator. These perforators are reliable and large enough to support long and large propeller flaps that will cover most defects in this region, while still allowing primary donor-site closure.
Keywords: internal mammary artery perforator; musculophrenic artery perforator; deep inferior epigastric perforator; anterior trunk; thorax; chest; abdomen